Customer perceptions of frontline employee service delivery: A study of Russian bank customer satisfaction and behavioural intentions. (May 2016) - Rod, Michel; Ashill, Nicholas J.; Gibbs, Tanya
Abstract: This study examines the nature of relationships between customer perceptions of frontline employee service delivery (core and relational), satisfaction and selected behavioural intentions by using customers of a commercial retail bank in Russia as its setting. Contrary to findings from North American-Western research, the study findings show that relational service delivery only significantly impacts customer satisfaction for Russian males whereas core service delivery only impacts this affective outcome for Russian female customers. Implications of the results are discussed and future research avenues are offered.